La questione del tempo in Burnt Norton di T.S. Eliot - Fabris, Adriano (Bollettino Filosofico, 2017)
n this paper a philosophical interpretation of T.S. Eliot’s Burnt Norton is developed. The topic of this interpretation is Eliot’s concept of “time”. In the first Quartet time is conceived neither as a sequence of “moments”, nor as a contingent dimension which is related to an upper, eternal level. On the contrary, according to Eliot’s thought, the same structure of time is an eternal dimension: like «the form, the pattern» of «a Chinese jar». By referring to this idea of time is possibile to avoid the «waste land» of contemporary common experience.